Unusual intramuscular locations as a first presentation of hydatid cyst disease in children: a report of two cases - Ruba A. Khasawneh; Ziyad M. Mohaidat; Rawand A. Khasawneh; Sohaib B. Zoghoul; Yousef M. Henawi (BMC, 2021)
Abstract Background Hydatid disease is an endemic disease in many countries of the world including the Middle East. It mainly affects the liver and lungs. Intramuscular hydatid disease is rarely reported in children. Such uncommon localization of hydatid cyst may pose difficulties in the clinical and radiological diagnosis; hence affecting patient's management and outcome even in endemic areas. Case presentation We herein describe intramuscular hydatid cysts in 2 different children. The first case is a 5-year-old boy who presented with a painless palpable lump over the right lumbar paraspinal region. His history was remarkable for sheep contact. His laboratory results revealed a mild increase in white blood cell (WBC) count and C-reactive protein. The lesion showed typical features of a hydatid cyst on ultrasound. Further imaging including ultrasound of the abdomen and CT of the chest, abdomen, and pelvis showed infestation of the liver and lung as well. The lesions were resected surgically without complications. The patient received Albendazole preoperatively and after surgery for 3 months. No evidence of recurrence was seen during follow-up. The second case is a 6-year-old girl who presented with an incidental palpable lump in her left thigh during her hospital admission for recurrent meningitis. Ultrasound and MRI imaging were performed demonstrating a unilocular cystic lesion in the left proximal rectus femoris muscle. A provisional diagnosis of hematoma vs. myxoma was given. Biopsy was performed and yielded blood products only. The lesion was resected surgically with a postoperative diagnosis of hydatid cyst. Blood tests performed afterward showed a positive titer for Echinococcus. The patient received Albendazole for 3 months. No evidence of recurrence was seen during follow-up. Conclusions Despite its rarity; skeletal muscle hydatid cyst should always be considered in the differential diagnosis of cystic muscle lesions in children in endemic areas even if imaging studies did not show any of the typical signs. This will improve patient outcome by preventing unnecessary cystic puncture which might lead to serious complications, such as anaphylaxis and local dissemination.